Help your kids with science a unique step-by-step visual guide (Dorling Kindersley London, 2012)
With clear graphics, instantly understandable diagrams, and welcoming, jargon-free text--covering all the important areas of biology, chemistry and physics--this comprehensive and stress-free approach to science is a great resource for children and adults to learn even the most complex science problems with confidence. Full color